2022
DOI: 10.1101/2022.12.22.521653
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Conserved NIMA kinases regulate multiple steps of endocytic trafficking

Abstract: Human NIMA-related kinases have primarily been studied for their roles in cell cycle progression (NEK1/2/6/7/9), checkpoint-DNA-damage control (NEK1/2/4/5/10/11), and ciliogenesis (NEK1/4/8). We previously showed that Caenorhabditis elegans NEKL-2 (NEK8/9 homolog) and NEKL-3 (NEK6/7 homolog) regulate apical clathrin-mediated endocytosis (CME) in the worm epidermis and are essential for molting. Here we show that NEKL-2 and NEKL-3 also have distinct roles in controlling endosome function and morphology. Specifi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 128 publications
0
11
0
Order By: Relevance
“…A recent publication demonstrated that knockdown of NEK7 in HeLa cells resulted in the dispersal of CI-MPR into endosomes, suggesting defective retrieval of this sorting receptor (Joseph et al, 2023). This phenotype is similar to the depletion of retromer (Arighi et al, 2004; Seaman, 2004) or Rab7A (Rojas et al, 2008; Seaman et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent publication demonstrated that knockdown of NEK7 in HeLa cells resulted in the dispersal of CI-MPR into endosomes, suggesting defective retrieval of this sorting receptor (Joseph et al, 2023). This phenotype is similar to the depletion of retromer (Arighi et al, 2004; Seaman, 2004) or Rab7A (Rojas et al, 2008; Seaman et al, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…Although it has been shown to phosphorylate Rab7A, it is not implicated in retromer recruitment. Recent work showed that in cells lacking NEK7, CI-MPR was distributed to punctate structures, rather than being primarily localized to the Golgi apparatus (Joseph et al, 2023). This led us to investigate the role of NEK7 in Rab7A serine 72 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…In prior studies we have shown that NEKL-2 and NEKL-3 localize to several endosomal trafficking compartments, that depletion of NEKL-2 and NEKL-3 leads to morphologically and functionally altered trafficking compartments, and that mutations in several membrane trafficking factors can suppress molting defects associated with nekl loss (YOCHEM et al 2015;LAZETIC AND FAY 2017a;LAZETIC et al 2018;JOSEPH et al 2020;JOSEPH et al 2023). Thus, it is possible that loss of catp-1 may lead to a partial suppression of nekl molting defects through direct or indirect effects on membrane trafficking.…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with these findings, our genetic screens identified conserved ankyrin-repeat partners of NEKL-2 (MLT-2/ANKS6 and MLT-4/INVS) and NEKL-3 (MLT-3/ANKS3) as required for molting, which we showed are necessary for proper NEKL subcellular localization (LAZETIC AND FAY 2017a). Further studies have indicated roles for NEKL-2 and NEKL-3 at multiple steps of membrane trafficking, including clathrin-mediated endocytosis and endosomal transport, and have implicated human NEK6 and NEK7 in analogous trafficking functions in tissue culture cells (JOSEPH et al 2020;JOSEPH et al 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Gene ontology analysis of the 179 PTPN-22::TurboID-associated proteins indicated statistically significant enrichment of proteins acting within various molecular and cellular structures including the actin cytoskeleton, germline P granules, the NatC/N-terminal protein acetyltransferase complex, and the spliceosomal small nuclear ribonucleoprotein (snRNP) Notably, whereas PTPN-22 was broadly expressed, the NEKLs and MLTs are expressed and required specifically for molting in the hyp7 epidermal syncytium (37)(38)(39). To identify PTPN-22associated proteins that act within hyp7, we also carried out proximity labeling studies, using three technical replicates, in which PTPN-22::TurboID was expressed under the control of a strong hyp7-specific promoter (Y37A1B.5; Phyp7::PTPN-22::TurboID) via a multicopy array (S3A…”
Section: Proximity Labeling Identifies Candidate In Vivo Ptpn-22 Inte...mentioning
confidence: 99%